Social constructions of gender in social media: Representations and their impact on students’ perceptions - Aqila Tristianti (Universitas Negeri Yogyakarta, 2025)
ABSTRACT The purpose of this study is to examine how gender is socially constructed via social media, with a special emphasis on how gender representation affects students’ perceptions. This study analyses a variety of scientific journals pertaining to gender and social media utilizing a qualitative approach and the literature review method. The results show that gender identity is significantly shaped and reconstructed by social media through a variety of explicit and implicit forms of expression. In addition to reinforcing gender stereotypes, these portrayals allow discussion on gender equality to prosper. Additionally, social media gives students a way to express themselves and explore and regulate their gender identities. Students’ ideas of gender roles have changed as a result of this construction, becoming more fluid and open. As a result, social media plays a significant part in influencing how students perceive gender in modern society. Keywords: gender, social media, social construction, representation, students